Negative electrode active material for nonaqueous electrolyte secondary battery and method for producing same

By using silicon compound particles covered with carbon coating as the negative electrode active material of lithium-ion secondary battery, the problem of expansion and contraction of silicon material during charging and discharging is solved, and the cycle characteristics and initial efficiency of the battery are improved.

CN119563244APending Publication Date: 2025-03-04SHIN ETSU CHEMICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055999.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-07-18
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When silicon is used as the negative electrode active substance in lithium-ion secondary batteries, expansion and contraction are easily caused during charging and discharging, resulting in surface rupture and irreversible capacity, thereby reducing the cycling characteristics and initial efficiency of the battery.

Method used

A negative electrode active material containing particles of silicon compound (SiOx: 0.5≤x≤1.6) is used, and the particles contain Li compounds, and at least a part thereof is covered with a carbon coating. The carbon coating is composed of a compound having an O-C=O bond and a C-C bond, and the coverage amount is between 0-1 mass %.

Benefits of technology

The capacity retention rate and initial efficiency of the battery are improved, the irreversible capacity during charging and discharging is reduced, and the stability and conductivity of the negative electrode active material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563244A_ABST
    Figure CN119563244A_ABST
Patent Text Reader

Abstract

The present invention is a negative electrode active material for a non-aqueous electrolyte secondary battery, the negative electrode active material comprising negative electrode active material particles, the negative electrode active material particles containing silicon compound particles, the silicon compound particles containing a silicon compound (SiOx: 0.5 < = x < = 1.6), the silicon compound particles containing a Li compound, at least a portion of the negative electrode active material particles are covered with a carbon coating film, and the amount of the carbon coating film covered on the negative electrode active material particles is more than 0% by mass but not more than 1% by mass with respect to the total of the silicon compound particles and the carbon coating film. The carbon coating film contains a coating film comprising at least one of a compound having an O-C = O bond and a compound having a C-C bond, and the silicon compound particles contain crystalline Li2SiO3 as the Li compound. As a result, it is possible to provide a negative electrode active material for nonaqueous electrolyte secondary batteries, which has high capacity and excellent cycle characteristics and initial efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode active material for a non-aqueous electrolyte secondary battery and a method for producing the same. Background Art

[0002] In recent years, small electronic devices represented by mobile terminals have become widely popular, and there is an urgent need for further miniaturization, lightness and long service life. In response to such market demand, a secondary battery that is particularly small, light and can obtain high energy density is being developed. This secondary battery can be used not only in small electronic devices, but also in large electronic devices represented by automobiles, and power storage systems represented by houses.

[0003] Among them, lithium-ion secondary batteries are highly anticipated because they are small and can be easily increased in capacity, and can achieve higher energy density than lead batteries, nickel-cadmium batteries, and the like.

[0004] The lithium ion secondary battery comprises a positive electrode, a negative electrode, a separator and an electrolyte. The negative electrode contains a negative electrode active material involved in charge and discharge reactions.

[0005] As the negative electrode active material, carbon materials (carbon-based active materials) are generally used. On the other hand, the battery capacity is required to be further improved according to the recent market demand. In order to increase the battery capacity, the use of silicon as a negative electrode active material is being studied. The reason is that the theoretical capacity of silicon (4199mAh / g) is more than 10 times that of graphite (372mAh / g), so a significant increase in battery capacity can be expected. The development of silicon materials as negative electrode active material materials is not limited to silicon monomers, and compounds represented by alloys, oxides, etc. have also been studied. In addition, with regard to the shape of the active material, for carbon-based active materials, studies have been conducted on standard coating types to integrated types directly deposited on the collector.

[0006] However, if silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charge and discharge, and is therefore prone to rupture mainly near the surface of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material a substance that is easily ruptured. If the surface of the negative electrode active material is ruptured, a new surface will be generated, and the reaction area of ​​the active material will increase. At this time, a decomposition reaction of the electrolyte will occur on the new surface, and a film as a decomposition product of the electrolyte will be formed on the new surface, so the electrolyte is consumed. Therefore, the cycle characteristics become prone to decline.

[0007] Previously, in order to improve the initial efficiency and cycle characteristics of the battery, attempts have been made to dope silicon oxide as a negative electrode active material with lithium (for example, refer to the following patent document 1). By making the silicon oxide as a negative electrode active material contain lithium, when such a negative electrode active material is used to make a negative electrode, the irreversible component can be reduced, so an improvement in the initial efficiency can be expected. In addition, the capacity of the lithium-ion secondary battery can be expected to increase through the improvement in the initial efficiency.

[0008] However, although the initial efficiency of silicon oxide as a negative electrode active material has been improved, it is still lower than that of existing positive electrode materials such as LiCoO2 (lithium cobalt oxide) (for example, see Patent Document 2), and therefore further efficiency improvement is required.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Application Publication No. 2011-222153

[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-113495 Summary of the invention

[0013] 1. Technical issues to be resolved

[0014] The present invention is completed in view of the above problems, and its purpose is to provide a negative electrode active material for a non-aqueous electrolyte secondary battery with high capacity, good cycle characteristics and initial efficiency. In addition, the present invention also aims to provide a method for manufacturing such a negative electrode active material for a non-aqueous electrolyte secondary battery.

[0015] (II) Technical solution

[0016] In order to achieve the above object, the present invention provides a negative electrode active material for a non-aqueous electrolyte secondary battery, which has negative electrode active material particles, wherein the negative electrode active material particles contain a silicon compound (SiO x :0.5≤x≤1.6), the silicon compound particles containing a Li compound, the negative electrode active material for a non-aqueous electrolyte secondary battery is characterized in that at least a portion of the negative electrode active material particles are covered with a carbon coating, and the coverage of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, the carbon coating includes a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond, and the silicon compound particles contain crystalline Li2SiO3 as the Li compound.

[0017] The negative electrode active material of the present invention includes negative electrode active material particles containing silicon compound particles, and thus has a high battery capacity. In addition, since the SiO2 component part of the silicon compound that is unstable when lithium is inserted and released during battery charging is pre-modified into other Li compounds, the irreversible capacity generated during charging and discharging can be reduced. In addition, the negative electrode active material particles have appropriate conductivity due to the inclusion of a carbon coating, which can improve the capacity retention rate and initial efficiency. Further, by making the coverage of the carbon coating greater than 0 mass% and less than 1 mass%, the capacity of the silicon compound particles will not be damaged, and a high-capacity negative electrode active material can be obtained. In addition, by including a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond, the bonding property of the binder when making an aqueous slurry can be improved. As a result, the battery characteristics can be improved. In addition, by including Li2SiO3 as a lithium compound that is stable to water, the generation of gas can be suppressed even in an aqueous slurry, and a stable state can be maintained, which results in an improvement in initial efficiency and capacity retention rate. In addition, the negative electrode active material particles containing silicon compound particles are also referred to as silicon-based active material particles. In addition, the negative electrode active material containing the silicon-based active material particles is also referred to as a silicon-based active material.

[0018] At this time, the intensity ratio of intensity Ia derived from OC═O bond at around 290 eV to intensity Ib derived from CC bond at around 285 eV obtained by X-ray photoelectron spectroscopy (XPS) of the negative electrode active material is preferably 0≤Ia / Ib≤3.0.

[0019] If Ia / Ib is within this range, the adhesiveness of the binder when making an aqueous slurry is improved, and the battery characteristics are improved as a result. If Ia / Ib is above 0, the compatibility with the slurry becomes good, the slurry dispersibility is improved, and the battery characteristics are improved as a result. On the other hand, if Ia / Ib is below 3.0, the side reactions on the surface of the active material during charge and discharge are suppressed, and the battery characteristics are improved.

[0020] In addition, it is preferred that the intensity Ie of the negative electrode active material derived from Li2SiO3 near 2θ=18.7° obtained by X-ray diffraction satisfies 1≤Ie / Ic≤18.5 relative to the intensity Ic derived from Si near 2θ=47.5°.

[0021] When the intensity ratio Ie / Ic is less than 18.5, the generation of gas in the aqueous slurry can be suppressed, and the stability of the slurry can be easily ensured. On the other hand, when the intensity ratio Ie / Ic is greater than 1, the doped Li is more stable, thereby suppressing the generation of gas in the aqueous slurry.

[0022] At this time, it is preferred that the half-value width of the peak derived from Li 2 SiO 3 at 2θ=18.7° obtained by X-ray diffraction of the negative electrode active material is 0.5° or more and 3.0° or less.

[0023] Thus, by making the half-peak width of the peak derived from Li2SiO3 near 2θ=18.7° obtained by X-ray diffraction greater than or equal to 0.5° and less than or equal to 3.0°, the elution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained.

[0024] Furthermore, in the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention, it is preferred that the crystallite size derived from the Si (220) crystal plane obtained by X-ray diffraction of the negative electrode active material is 5 nm or less.

[0025] As long as the crystallite size derived from the Si (220) crystal plane is within the above range, better battery characteristics can be obtained.

[0026] In addition, it is preferred that the negative electrode active material is 29 The chemical shift values ​​obtained by the Si-MAS-NMR spectrum have at least one peak in at least one region among the region of -80 ppm to less than -70 ppm, the region of -70 ppm to less than -60 ppm, and the region of -60 ppm to less than -30 ppm.

[0027] The peak near the chemical shift value of -60ppm or more and less than -30ppm comes from a silicon oxide with a low valence number, the peak near -70ppm or more and less than -60ppm comes from the Li6Si2O7 component, and the peak near -80ppm or more and less than -70ppm comes from the Li2SiO3 component. Therefore, by having at least one or more peaks in at least one region in the above-mentioned region, it is possible to suppress the dissolution of alkaline components into the aqueous slurry, and better battery characteristics can be obtained. In addition, as a peak near the region of -70ppm or more and less than -60ppm, it can be a peak from the Li6Si2O7 component, but it is more preferably substantially absent. That is, compared with the peak near the region having -70ppm or more and less than -60ppm, it is more preferably present in at least any one of the peaks near -60ppm or more and less than -30ppm and the peaks near -80ppm or more and less than -70ppm.

[0028] At this time, the negative electrode active material is 29When the peak intensity of the peak obtained in the region where the chemical shift value obtained by the Si-MAS-NMR spectrum is greater than -60ppm and less than -30ppm is set to If, the peak intensity of the peak obtained in the region where the chemical shift value is greater than -70ppm and less than -60ppm is set to Ih, and the peak intensity of the peak obtained in the region where the chemical shift value is greater than -80ppm and less than -70ppm is set to Ii, the following conditions are satisfied: 0≤If / Ii≤0.23 and 0≤Ih / Ii≤1.1.

[0029] Such silicon compound particles with NMR peaks can inhibit the dissolution of alkaline components into aqueous slurries, and can obtain better battery characteristics. In addition, as mentioned above, the peak near the region above -70ppm and less than -60ppm is the peak from the Li6Si2O7 component, and it is preferred that the peak does not exist substantially, and more preferably Ih / Ii=0.

[0030] In the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention, it is preferred that the intensity ratio Id / Ig of the D band to the G band obtained by Raman spectroscopy of the negative electrode active material is 0≤Id / Ig≤2.0.

[0031] Therefore, if 0≤Id / Ig≤2.0, the peeling of the carbon film and the side reaction on the carbon surface due to expansion and contraction can be suppressed, so that better battery characteristics can be obtained.

[0032] Furthermore, it is preferred that the negative electrode active material have a ratio ISi / Ig of the intensity of the Si peak to the intensity of the G band obtained by Raman spectroscopy analysis such that 0≤ISi / Ig≤5.0.

[0033] Therefore, if 0≤ISi / Ig≤5.0, the surface exposure of the silicon-based compound particles can be suppressed and the generation of gas in the aqueous slurry can be delayed, resulting in better battery characteristics.

[0034] Furthermore, it is preferred that the silicon compound particles have a median particle size of 0.5 μm or more and 20 μm or less.

[0035] If the median particle size is 0.5 μm or more, the surface area of ​​the silicon compound particles that can cause side reactions is small, so Li will not be consumed excessively, and the battery cycle retention rate can be highly maintained. In addition, if the median particle size is 20 μm or less, the expansion during Li insertion is small, and it is not easy to break and crack. Furthermore, the silicon compound particles have a small expansion, so for example, the negative electrode active material layer formed by mixing a commonly used silicon-based active material with a carbon active material is not easily damaged.

[0036] In addition, the negative electrode active material particles do not contain Li2CO3, or a portion of their outermost layer is covered with crystalline Li2CO3, and the peak intensity Ij of the negative electrode active material particles obtained by X-ray diffraction originating from Li2CO3 near 2θ=21° satisfies 0≤Ij / Ic≤10 relative to the intensity Ic originating from Si near 2θ=47.5°.

[0037] When the outermost layer of the negative electrode active material particles contains crystalline Li2CO3 ionic substances, the binding property of the binder when the aqueous slurry is prepared is improved. When Ij / Ic≤10, when the aqueous slurry is prepared, the pH of the slurry can be set within an appropriate range, and the generation of gas and the decrease in the viscosity of the slurry can be suppressed. In addition, from the perspectives of improving the binding property of the binder and increasing the pH, it is preferred that substantially no crystalline Li2CO3 is contained.

[0038] Furthermore, in the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention, it may be covered with a carbon layer different from the carbon coating.

[0039] In the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention, it is preferred that the peak derived from the G band obtained by Raman spectroscopy of the negative electrode active material is 1588 cm -1 ~1598cm -1 of carbon film covering.

[0040] The peak derived from the G band obtained by analyzing the outermost layer of the silicon compound by Raman spectroscopy was 1588 cm -1 ~1598cm -1 The carbon film covering can ensure better conductivity and thus achieve better battery characteristics.

[0041] Furthermore, in order to achieve the above object, the present invention provides a non-aqueous electrolyte secondary battery, characterized in that it contains any one of the above-mentioned negative electrode active materials for non-aqueous electrolyte secondary batteries.

[0042] Such a secondary battery has high cycle retention rate and initial efficiency and can be manufactured with industrial advantages.

[0043] Furthermore, the present invention provides a mobile terminal, an electric vehicle, and a power storage system, each of which is characterized by comprising the above-mentioned nonaqueous electrolyte secondary battery.

[0044] The nonaqueous electrolyte secondary battery including the negative electrode active material for a nonaqueous electrolyte secondary battery of the present invention can be used in these applications.

[0045] In addition, in order to achieve the above-mentioned object, the present invention provides a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, which is a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery containing negative electrode active material particles, characterized in that the production method comprises: preparing a silicon compound (SiO x :0.5≤x≤1.6) and a process of inserting Li into the silicon compound particles to generate Li2SiO3 as a Li compound, wherein, at the same time as or after the process of inserting Li into the silicon compound particles, there is further included a process of covering at least a portion of the silicon compound particles with a carbon coating, wherein the covering with the carbon coating is performed in the following manner: relative to the total of the silicon compound particles and the carbon coating, the coverage amount of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass %, and the carbon coating is a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond.

[0046] According to such a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, it is possible to obtain a non-aqueous negative electrode active material having a high battery capacity and a good cycle retention rate by utilizing the original characteristics of silicon oxide modified with Li.

[0047] In this case, the step of inserting Li into the silicon compound particles is preferably performed by an electrochemical method or a method based on a redox reaction.

[0048] (III) Beneficial effects

[0049] The negative electrode active material of the present invention can improve the stability of the slurry when manufacturing a secondary battery. As long as the slurry is used, a coating film that can be used industrially can be formed, thereby substantially improving the battery capacity, cycle characteristics and initial charge and discharge characteristics. In addition, the secondary battery of the present invention comprising the negative electrode active material can be produced with industrial advantages, and the battery capacity, cycle characteristics and initial charge and discharge characteristics are good. In addition, in electronic devices such as mobile terminals, power tools, electric vehicles and power storage systems using the secondary battery of the present invention, the same effect can be obtained.

[0050] Furthermore, the method for producing a negative electrode active material of the present invention can produce a negative electrode material that can improve the stability of the prepared slurry when manufacturing a secondary battery and can improve the battery capacity, cycle characteristics, and initial charge and discharge characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a cross-sectional view showing an example of the structure of a negative electrode for a non-aqueous electrolyte secondary battery including the negative electrode active material of the present invention.

[0052] Figure 2 This is a bulk modification device that can be used when producing the negative electrode active material of the present invention.

[0053] Figure 3 It is an exploded view showing a configuration example (laminated film type) of a lithium ion secondary battery including the negative electrode active material of the present invention. DETAILED DESCRIPTION

[0054] Hereinafter, the present invention will be described based on embodiments, but the present invention is not limited thereto.

[0055] As described above, as a means of increasing the battery capacity of a lithium-ion secondary battery, a method of using a negative electrode using a silicon-based active material as a main material as a negative electrode of a lithium-ion secondary battery has been studied. A lithium-ion secondary battery using a silicon-based active material as a main material is expected to have an initial efficiency and cycle characteristics close to those of a lithium-ion secondary battery using a carbon material (carbon-based negative electrode active material), but no negative electrode material has been proposed that can exhibit the same cycle stability as a non-aqueous electrolyte secondary battery using a carbon material (carbon-based negative electrode active material). In addition, the initial efficiency of silicon compounds containing oxygen is low, especially compared to carbon materials (carbon-based negative electrode active materials), so the improvement of their battery capacity is limited.

[0056] Therefore, the inventors of the present application conducted intensive studies to obtain a negative electrode active material that can easily manufacture a non-aqueous electrolyte secondary battery with high battery capacity and good cycle characteristics and initial efficiency, and thus completed the present invention.

[0057] [Negative Electrode Active Material of the Present Invention]

[0058] The negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention comprises negative electrode active material particles. In addition, the negative electrode active material particles contain a silicon compound (SiO x :0.5≤x≤1.6). Further, the silicon compound particles contain a Li compound. In addition, at least a portion of the negative electrode active material particles is covered with a carbon coating, and the coverage of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, and the carbon coating includes a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond. In addition, the silicon compound particles contain crystalline Li2SiO3 as the Li compound.

[0059] Since such a negative electrode active material includes negative electrode active material particles containing silicon compounds, it has a high battery capacity. In addition, since the SiO2 component part of the silicon compound that is unstable when lithium is inserted and released during battery charging is pre-modified into other Li compounds, the irreversible capacity generated during charging and discharging can be reduced. In addition, a carbon coating is included, and the carbon coating amount is greater than 0% by mass and less than 1% by mass relative to the total of the silicon compound and the carbon coating layer, so it can have appropriate conductivity and will not damage the capacity. As a result, high capacity and high capacity retention rate and initial efficiency are formed. In addition, by including a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond, the adhesion to the binder is improved. As a result, the battery characteristics are improved. Further, by including Li2SiO3 as a lithium compound that is stable to water, the generation of gas can be suppressed even in an aqueous slurry, and a stable state can be maintained, which can improve the initial efficiency and capacity retention rate. XPS determination can be performed, for example, under the following conditions.

[0060] XPS

[0061] Device: X-ray photoelectron spectroscopy device

[0062] X-ray source: monochromatic Al Kα ray

[0063] X-ray spot diameter: 100μm

[0064] Argon ion gun sputtering conditions: 0.5 kV 2mm×2mm.

[0065] [Constitution of negative electrode]

[0066] Next, the structure of the negative electrode of the secondary battery including the negative electrode active material of the present invention will be described.

[0067] Figure 1 1 is a cross-sectional view of a negative electrode including the negative electrode active material of the present invention. Figure 1 As shown, the negative electrode 10 has a negative electrode active material layer 12 on a negative electrode collector 11. The negative electrode active material layer 12 may be provided on both sides or only on one side of the negative electrode collector 11. Furthermore, as long as the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention is used, the negative electrode collector 11 may not be provided.

[0068] [Negative electrode current collector]

[0069] The negative electrode current collector 11 is an excellent conductive material and is composed of a material with high mechanical strength. Examples of conductive materials that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). The conductive material is preferably a material that does not form an intermetallic compound with lithium (Li).

[0070] The negative electrode current collector 11 preferably contains carbon (C) or sulfur (S) in addition to the main elements. This is to improve the physical strength of the negative electrode current collector. In particular, when there is an active material layer that expands during charging, as long as the current collector contains the above elements, it has the effect of suppressing deformation of the electrode including the current collector. The content of the above-mentioned elements is not particularly limited, and is preferably less than 100 ppm. The reason is that a higher deformation suppression effect can be obtained.

[0071] In addition, the surface of the negative electrode current collector 11 may be roughened or not. A roughened negative electrode current collector may be, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched. An unroughened negative electrode current collector may be, for example, a rolled metal foil.

[0072] [Negative Electrode Active Material Layer]

[0073] The negative electrode active material layer 12 may include a variety of negative electrode active materials such as carbon-based active materials in addition to silicon-based active material particles. Furthermore, in terms of battery design, other materials such as thickeners (also known as "adhesives" or "binders") and conductive additives may be included. In addition, the shape of the negative electrode active material may be granular.

[0074] In addition, as described above, the negative electrode active material of the present invention comprises SiO x (0.5≤x≤1.6). The silicon-based active material particles are made of silicon oxide material (SiO x : 0.5≤x≤1.6), and as its composition, x is preferably close to 1. This is because high cycle characteristics can be obtained. In addition, the composition of the silicon oxide material of the present invention does not necessarily mean that the purity is 100%, and it may also contain trace amounts of impurity elements or Li.

[0075] In addition, in the present invention, the lower the crystallinity of the silicon compound (the crystallinity of Si crystallites), the better. Specifically, when the negative electrode active material is measured by X-ray diffraction using Cu-Kα rays, the crystallite size derived from the Si (220) crystal plane obtained by the X-ray diffraction is preferably 5 nm or less. In addition, it is preferred that the half-peak width of the diffraction peak derived from the Si (220) crystal plane obtained by X-ray diffraction is 1.5° or more. It is particularly preferred that the diffraction peak is wide and does not have a clear peak. Thus, by making the crystallinity low and the amount of Si crystals present small, not only can the battery characteristics be improved, but also a stable Li compound can be generated.

[0076] The crystallite size derived from the Si (220) crystal plane can be calculated by XRD peak analysis. The calculation of the crystallite size based on XRD can be performed, for example, under the following conditions. For the broad peak, the analysis software TOPAS can be used, for example, under the following conditions.

[0077] XRD determination

[0078] Device: D2 PHASER manufactured by Bruker

[0079] X-ray source: Cu

[0080] Divergence slit: 0.5°

[0081] ·Incident side light: 4°

[0082] · Side light: 4°

[0083] Calculation of crystallite size

[0084] Analysis software: DIFFRAC. TOPAS

[0085] Analysis method: Peak fitting method

[0086] Emission Profile: CuKa5.1am

[0087] Function: FP (First Principle) function

[0088] Refinement Option: Select "Calculateerror", "Useextrapolation"

[0089] In addition, the median particle size of the silicon compound particles is not particularly limited, among which it is preferably greater than 0.5 μm and less than 20 μm (volume basis). This is because, if it is within this range, it will become easy to adsorb and release lithium ions during charging and discharging, and the silicon-based active material particles will become less likely to break. As long as the median particle size is greater than 0.5 μm, the surface area will not become too large, so it is not easy to cause side reactions during charging and discharging, and the irreversible capacity of the battery can be reduced. On the other hand, if the median particle size is less than 20 μm, the silicon-based active material particles will become less likely to break and thus less likely to generate new surfaces, so it is preferred.

[0090] Furthermore, in the present invention, as the Li compound contained in the silicon compound, in addition to Li2SiO3, Li4SiO4 and Li6Si2O7 may also exist. 4、Li silicates of Li6Si2O7 are more stable than other Li compounds, so silicon-based active materials containing these Li compounds can obtain more stable battery characteristics. These Li compounds can be obtained by selectively changing part of the SiO2 component generated inside the silicon compound to a Li compound to modify the silicon compound.

[0091] The amount of Li compound in the negative electrode active material particles and the silicon compound particles can be quantified by NMR (nuclear magnetic resonance). NMR measurement can be performed, for example, under the following conditions.

[0092] 29 Si-MAS-NMR spectroscopy (Magic Angle Spinning Nuclear Magnetic Resonance)

[0093] · Device: 700NMR spectrometer manufactured by Bruker

[0094] Probe: 4mm HR-MAS rotor 50μL

[0095] Sample rotation speed: 10 kHz

[0096] ·Measurement environment temperature: 25℃

[0097] In addition, in the present invention, when modifying the silicon compound, an electrochemical method or a method for modification based on a redox reaction can be used. In particular, when the silicon compound is modified using an electrochemical method and a modification based on redox, the battery characteristics of the negative electrode active material are improved. In addition, in the modification, not only Li is inserted into the silicon compound, but also the stabilization of the Li compound based on heat treatment and the detachment of Li from the silicon compound can be combined. As a result, the water resistance of the negative electrode active material and the stability of the slurry will be further improved. In addition, the silicon compound modification can also be combined with thermal doping as a physical method. However, in the negative electrode active material of the present invention, the coverage of the carbon coating on the negative electrode active material particles needs to be greater than 0% by mass and less than 1% by mass relative to the total of the silicon compound particles and the carbon coating. In addition, the carbon coating needs to be a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond.

[0098] In addition, in the negative electrode active material of the present invention, it is preferred that the silicon compound 29The chemical shift values ​​obtained by Si-MAS-NMR spectrum have a peak from the low-valence region of the obtained silicon oxide near the region of -60ppm or more and less than -30ppm, a peak from the obtained Li6Si2O7 region near the region of -70ppm or more and less than -60ppm, and a peak from the obtained Li2SiO3 region near the region of -70ppm or more and less than -60ppm. Thus, the stability of the slurry can be further improved by forming Li silicate through modification.

[0099] Furthermore, as described above, in the present invention, since the silicon compound particles in the silicon-based active material particles include a carbon coating on at least a portion of the surface, appropriate conductivity can be obtained.

[0100] In addition, in the negative electrode active material of the present invention, the intensity ratio of the intensity Ia derived from the OC=O bond near 290eV obtained by X-ray photoelectron spectroscopy (XPS) of the negative electrode active material to the intensity Ib derived from the CC bond near 285eV is preferably 0≤Ia / Ib≤3.0. As long as Ia / Ib is within this range, the adhesion of the binder when the aqueous slurry is made is improved, and as a result, the battery characteristics are improved. As long as Ia / Ib is above 0, the compatibility with the slurry becomes good and the slurry dispersibility is improved, and as a result, the battery characteristics are improved. On the other hand, as long as Ia / Ib is below 3.0, the side reactions on the surface of the active material during charge and discharge are suppressed, and the battery characteristics are improved.

[0101] In addition, it is preferred that the intensity Ie of the negative electrode active material of the present invention derived from Li2SiO3 near 2θ=18.7° obtained by X-ray diffraction relative to the intensity Ic derived from Si near 2θ=47.5° satisfies 1≤Ie / Ic≤18.5. When the intensity ratio Ie / Ic is less than 18.5, the generation of gas in the aqueous slurry can be suppressed, and the stability of the slurry can be easily ensured. On the other hand, when the intensity ratio Ie / Ic is greater than 1, the doped Li is more stable and the generation of gas in the aqueous slurry can be suppressed.

[0102] In addition, the half-peak width of the peak near 2θ=18.7° derived from Li2SiO3 obtained by X-ray diffraction of the negative electrode active material is preferably 0.5° or more and 3.0° or less. This can inhibit the dissolution of alkaline components into the aqueous slurry and obtain better battery characteristics.

[0103] In addition, it is preferred that the negative electrode active material of the present invention is 29The chemical shift values ​​obtained by the Si-MAS-NMR spectrum have at least one peak in at least one region among the region of -80 ppm to less than -70 ppm, the region of -70 ppm to less than -60 ppm, and the region of -60 ppm to less than -30 ppm.

[0104] The peak with a chemical shift value of more than -60ppm and less than -30ppm comes from a low-valence silicon oxide, more than -70ppm and less than -60ppm comes from a Li6Si2O7 component, and more than -80ppm and less than -70ppm comes from a Li2SiO3 component. Therefore, by having at least one peak in at least one region in the above-mentioned region, the dissolution of alkaline components into the aqueous slurry can be suppressed, and better battery characteristics can be obtained. In addition, as a peak near a region of more than -70ppm and less than -60ppm, it can be a peak from the Li6Si2O7 component, but it is more preferably substantially absent. Compared with the peak near a region having more than -70ppm and less than -60ppm, it is more preferably present in at least any one of the peaks near a region having more than -60ppm and less than -30ppm and a peak near a region having more than -80ppm and less than -70ppm.

[0105] At this time, the negative electrode active material is 29 When the peak intensity of the peak obtained in the region where the chemical shift value obtained by the Si-MAS-NMR spectrum is greater than -60ppm and less than -30ppm is set to If, the peak intensity of the peak obtained in the region where the chemical shift value is greater than -70ppm and less than -60ppm is set to Ih, and the peak intensity of the peak obtained in the region where the chemical shift value is greater than -80ppm and less than -70ppm is set to Ii, the following conditions are satisfied: 0≤If / Ii≤0.23 and 0≤Ih / Ii≤1.1.

[0106] These silicon compound particles having such NMR peaks can inhibit the dissolution of alkaline components into aqueous slurries, and can obtain better battery characteristics. In addition, as mentioned above, the peak near the region of -70ppm or more and less than -60ppm is the peak from the Li6Si2O7 component, and it is preferred that the peak does not exist substantially, and more preferably Ih / Ii=0.

[0107] In addition, in the negative electrode active material for the non-aqueous electrolyte secondary battery of the present invention, the intensity ratio Id / Ig of the D band and the G band obtained by Raman spectroscopy of the negative electrode active material is preferably 0≤Id / Ig≤2.0. Thus, if 0≤Id / Ig≤2.0, the peeling of the carbon film or the side reaction on the carbon surface caused by expansion and contraction can be suppressed, so that better battery characteristics can be obtained.

[0108] In addition, the intensity ratio ISi / Ig of the Si peak intensity and the G band obtained by Raman spectroscopy of the negative electrode active material is preferably 0≤ISi / Ig≤5.0. Therefore, if 0≤ISi / Ig≤5.0, the surface exposure of the silicon compound particles can be suppressed, and the generation of gas in the aqueous slurry can be delayed, so that better battery characteristics can be obtained as a result.

[0109] In addition, the negative electrode active material particles do not contain Li2CO3, or a portion of their outermost layer is covered with crystalline Li2CO3 and the peak intensity Ij of the negative electrode active material particles obtained by X-ray diffraction originating from Li2CO3 near 2θ=21° satisfies 0≤Ij / Ic≤10 relative to the intensity Ic originating from Si near 2θ=47.5°.

[0110] When the outermost layer of the negative electrode active material particles contains a crystalline Li2CO3 ionic substance, the binding property of the binder when the aqueous slurry is prepared is improved. When Ij / Ic≤10, when the aqueous slurry is prepared, the pH of the slurry can be set within an appropriate range, and the generation of gas and the decrease in the viscosity of the slurry can be suppressed. In addition, considering the two aspects of the improvement of the binding property of the binder and the increase in pH, it is preferred that substantially no crystalline Li2CO3 is contained.

[0111] Furthermore, the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention can be coated with a carbon layer different from the carbon coating.

[0112] In the negative electrode active material for a non-aqueous electrolyte secondary battery of the present invention, the negative electrode active material preferably has a peak derived from the G band at 1588 cm-1 as determined by Raman spectroscopy. -1 ~1598cm -1 The top layer of the silicon compound is covered with a carbon film. The peak from the G band obtained by Raman spectroscopy is 1588 cm -1 ~1598cm -1 The carbon film covering can ensure better conductivity and thus obtain better battery characteristics.

[0113] [Method for manufacturing negative electrode]

[0114] Next, an example of a method for producing a negative electrode of a nonaqueous electrolyte secondary battery of the present invention will be described.

[0115] First, a method for producing a negative electrode material included in the negative electrode will be described.

[0116] First, a silicon compound (SiO x:0.5≤x≤1.6). Then, Li is inserted into the silicon compound particles to generate Li2SiO3 as a Li compound. In the present invention, at the same time as or after the process of inserting Li into the silicon compound particles, a process of covering at least a portion of the silicon compound particles with a carbon coating is further included. At this time, the carbon coating is covered in such a manner that the coverage amount of the carbon coating on the negative electrode active particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, and the carbon coating is a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond.

[0117] More specifically, the negative electrode active material is produced, for example, by the following steps.

[0118] First, the raw material for generating silicon oxide gas is heated in the temperature range of 900°C to 1600°C in the presence of an inert gas or under reduced pressure to generate silicon oxide gas. At this time, the raw material is a mixture of metal silicon powder and silicon dioxide powder. Considering the surface oxygen of the metal silicon powder and the presence of trace oxygen in the reactor, the desired mixing molar ratio is in the range of 0.8 < metal silicon powder / silicon dioxide powder <1.3. The Si crystallites in the particles can be controlled by changing the feed range, the vaporization temperature, or the heat treatment after generation. The generated gas is deposited on the adsorption plate. The deposit is taken out after the temperature in the reactor is lowered to below 100°C, and crushed and powdered using a ball mill, a jet mill, or the like.

[0119] Next, Li is inserted into the silicon active material particles prepared as described above to generate Li2SiO3 as a Li compound. In this case, in addition to Li2SiO3, one or more of Li6Si2O7 and Li4SiO4 may be contained. The insertion of Li is preferably performed by an electrochemical method or a redox method.

[0120] In the modification by the electrochemical method, the device structure is not particularly limited, but for example, it can be used Figure 2The bulk modification device 20 shown in the figure is used for bulk modification. The bulk modification device 20 comprises: a bath 27 filled with an organic solvent 23, an anode (lithium source, modification source) 21 arranged in the bath 27 and connected to one side of a power source 26, a powder storage container 25 arranged in the bath 27 and connected to the other side of the power source 26, and a diaphragm 24 provided between the anode 21 and the powder storage container 25. Silicon oxide powder 22 is stored in the powder storage container 25. In addition, silicon compounds (silicon oxide particles) are stored in the powder storage container, and voltage is applied to the powder storage container storing silicon oxide particles and the anode (lithium source) by the power supply. As a result, lithium can be inserted into and separated from the silicon compound particles, so that the silicon oxide powder 22 can be modified. By heat-treating the obtained silicon oxide at 400-800°C, the Li compound can be stabilized.

[0121] As the organic solvent 23 in the bath 27, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. can be used. In addition, as the electrolyte salt contained in the organic solvent 23, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), etc. can be used.

[0122] A lithium (Li) foil or a Li-containing compound may be used as the anode 21. Examples of the Li-containing compound include lithium carbonate, lithium oxide, lithium cobalt oxide, lithium iron olivine, lithium nickel oxide, and lithium vanadium phosphate.

[0123] After the electrochemical Li doping modification, the slurry can be washed with alkaline water, alcohol, weak acid or pure water dissolved with lithium carbonate, lithium oxide or lithium hydroxide. By washing, the excess alkaline components can be dissolved and the slurry stability can be improved.

[0124] In the modification based on the redox method, for example, lithium can be inserted by first immersing the silicon active material particles in a solution A in which lithium is dissolved in an ether solvent. The solution A may further contain a polycyclic aromatic compound or a linear polyphenylene compound. The Li compound can be stabilized by heat treating the obtained silicon oxide at 400~800°C. In addition, after the insertion of lithium, the active lithium can be separated from the silicon active material particles by immersing the silicon active material particles in a solution B containing a polycyclic aromatic compound or a linear polyphenylene compound or a derivative thereof. The solvent of the solution B can be, for example, an ether solvent, a ketone solvent, an ester solvent, an alcohol solvent, an amine solvent or a mixed solvent of these solvents. It can also be washed with alkaline water, alcohol, weak acid or pure water in which lithium carbonate, lithium oxide or lithium hydroxide is dissolved. By washing, the excess alkaline components can be dissolved and the slurry stability is improved.

[0125] As the ether solvent used for solution A, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether or a mixed solvent thereof can be used. Among them, tetrahydrofuran, dioxane, 1,2-dimethoxyethane and diethylene glycol dimethyl ether are particularly preferably used. These solvents are preferably dehydrated, and particularly preferably deoxygenated.

[0126] In addition, as the polycyclic aromatic compound contained in solution A, one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene and their derivatives can be used, and as the linear polyphenylene compound, one or more of biphenyl, terphenyl and their derivatives can be used.

[0127] As the polycyclic aromatic compound contained in the solution B, one or more of naphthalene, anthracene, phenanthrene, naphthalene, pentacene, pyrene, triphenylene, coronene, chrysene and derivatives thereof can be used.

[0128] As the ether solvent of solution B, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixed solvent thereof can be used.

[0129] As the ketone solvent, acetone, acetophenone, etc. can be used.

[0130] As the ester solvent, methyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, and the like can be used.

[0131] As the alcohol solvent, methanol, ethanol, propanol, isopropanol, etc. can be used.

[0132] As the amine solvent, methylamine, ethylamine, ethylenediamine, and the like can be used.

[0133] When Li doping is performed based on these electrochemical methods or redox reactions, a film derived from the carbon component contained in the reaction solution is generated. The film can be a film composed of at least one of a compound having an OC=O bond and a compound having a CC bond. In addition, after Li doping based on the above electrochemical method or redox reaction, the film can also be made into a film composed of at least one of a compound having an OC=O bond and a compound having a CC bond by heat treatment.

[0134] In addition, when the coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond, which is necessary for the negative electrode active material of the present invention, is formed by Li doping based on the above-mentioned electrochemical method or redox reaction, in addition to these methods, Li doping can also insert Li into the negative electrode active material particles by a hot doping method. At this time, for example, the negative electrode active material particles are mixed with LiH powder or Li powder and heated in a non-oxidizing atmosphere, so that they can be modified. As a non-oxidizing atmosphere, for example, an Ar (argon) atmosphere can be used. More specifically, first, LiH powder or Li powder is fully mixed with silicon oxide powder under an Ar atmosphere, sealed, and then homogenized by stirring each sealed container. Then, it is heated in the range of 700~750°C for modification. In addition, at this time, in order to separate Li from the silicon compound, the heated powder can be fully cooled, and then washed with alkaline water, alcohol, weak acid or pure water dissolved with lithium carbonate, lithium oxide, lithium hydroxide, etc. By washing, the excess alkaline components can be dissolved, and the slurry stability is improved.

[0135] Furthermore, a carbon layer (also referred to as a "second carbon layer") different from the carbon coating may be formed on the surface of the powder material obtained after lithium insertion. This carbon layer is effective in further improving the battery characteristics of the negative electrode active material.

[0136] As a method for forming a carbon layer (second carbon layer) on the surface of the powder material, thermal decomposition CVD is desirable. Thermal decomposition CVD is to place silicon oxide powder in a furnace, fill the furnace with hydrocarbon gas, and raise the temperature in the furnace. The decomposition temperature is not particularly limited, but it is particularly desirable to be below 1000°C. It is more desirable to be below 950°C, which can suppress the unplanned inhomogeneity of silicon oxide. The hydrocarbon gas is not particularly limited, but it is desirable that I C n H m In the composition, 2 ≥ n. This is because the production cost is low and the physical properties of the decomposition product are good.

[0137] <Aqueous Negative Electrode Slurry Composition>

[0138] After mixing the negative electrode active material prepared in the above manner with other materials such as a negative electrode binder and a conductive aid as needed, water (in addition to water, an organic solvent, etc. can also be added) can be added to obtain an aqueous negative electrode slurry composition. By using such an aqueous negative electrode slurry composition to prepare a negative electrode, a secondary battery with high capacity and good initial charge and discharge characteristics can be prepared.

[0139] Next, the aqueous negative electrode slurry composition is applied to the surface of the negative electrode current collector and dried to form a negative electrode active material layer. At this time, thermocompression bonding or the like may be performed as required. In the above manner, the negative electrode can be manufactured.

[0140] <Lithium-ion secondary battery>

[0141] Next, a laminated film type lithium ion secondary battery will be described as a specific example of the nonaqueous electrolyte secondary battery of the present invention.

[0142] [Construction of laminated film type secondary battery]

[0143] like Figure 3 The laminated film type lithium ion secondary battery 30 shown is mainly formed by accommodating a wound electrode body 31 inside a sheet-like outer casing 35. The wound electrode body 31 has a separator between the positive electrode and the negative electrode and is wound. In addition, there is also a case where a laminated body with a separator between the positive electrode and the negative electrode is not wound but is accommodated. In any electrode body, a positive electrode lead 32 is installed on the positive electrode, and a negative electrode lead 33 is installed on the negative electrode. The outermost periphery of the electrode body can be protected by a protective tape.

[0144] The positive electrode lead 32 and the negative electrode lead 33 are drawn out in one direction from inside to outside of the outer casing 35. The positive electrode lead 32 is made of a conductive material such as aluminum, and the negative electrode lead 33 is made of a conductive material such as nickel or copper.

[0145] The outer packaging member 35 is, for example, a laminated film in which a welding layer, a metal layer, and a surface protective layer are sequentially stacked, and in the laminated film, the outer peripheral portions of the welding layers of two films are bonded to each other by welding or a bonding agent so that the welding layer faces the electrode body 31. The welding portion is, for example, a film of polyethylene or polypropylene, and the metal portion is, for example, aluminum foil. The protective layer is, for example, nylon.

[0146] Between the outer casing 35 and the positive and negative electrode leads, a sealing film 34 is inserted to prevent the intrusion of external air. The material of the sealing film 34 is, for example, polyethylene, polypropylene, or polyolefin resin.

[0147] The positive electrode is Figure 1 The negative electrode 10 similarly has a positive electrode active material layer on both surfaces or on one surface of a positive electrode current collector.

[0148] The positive electrode current collector is formed of a conductive material such as aluminum.

[0149] The positive electrode active material layer includes any one or more of the positive electrode materials capable of absorbing and releasing lithium ions, and may also include other materials such as a positive electrode binder, a positive electrode conductive aid, and a dispersant according to the design. In this case, the details of the positive electrode binder and the positive electrode conductive aid are, for example, the same as the negative electrode binder and the negative electrode conductive aid described above.

[0150] As the positive electrode material, a lithium-containing compound is desirable. Examples of the lithium-containing compound include composite oxides composed of lithium and transition metal elements, or phosphate compounds containing lithium and transition metal elements. Among these positive electrode materials, compounds containing at least one of nickel, iron, manganese, and cobalt are preferred. As their chemical formulas, for example, Li x M1O2 or Li y M2PO4 represents. In the formula, M1 and M2 represent at least one transition metal element. The values ​​of x and y represent different values ​​depending on the charge and discharge state of the battery, but are generally represented by 0.05≤x≤1.10 and 0.05≤y≤1.10.

[0151] Examples of composite oxides containing lithium and transition metal elements include lithium cobalt composite oxides (Li x CoO2), lithium nickel composite oxide (Li x NiO2), lithium nickel cobalt composite oxide, etc. Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).

[0152] Examples of the phosphate compound containing lithium and a transition metal element include lithium iron phosphate compound (LiFePO4) and lithium manganese iron phosphate compound (LIFePO4). 1-u Mn u PO4 (0<u<1)) etc. When these positive electrode materials are used, high battery capacity and excellent cycle characteristics can be obtained.

[0153] [negative electrode]

[0154] The negative electrode has the same Figure 1 The negative electrode 10 for lithium ion secondary batteries has the same structure as that of the negative electrode 10, for example, a negative electrode active material layer is provided on both sides of the current collector. The negative electrode preferably has a negative electrode charge capacity greater than the capacity obtained from the positive electrode active material agent (as the charge capacity of the battery). Thus, the precipitation of lithium metal on the negative electrode can be suppressed.

[0155] The positive electrode active material layer is disposed on a portion of both sides of the positive electrode collector, and similarly, the negative electrode active material layer is also disposed on a portion of both sides of the negative electrode collector. In this case, for example, the negative electrode active material layer preferably disposed on the negative electrode collector is provided with an area where there is no positive electrode active material layer relative thereto. This is for a stable battery design.

[0156] In the region where the negative electrode active material layer and the positive electrode active material layer are not opposite to each other, they are hardly affected by charge and discharge. Therefore, the state of the negative electrode active material layer is maintained in the state just after it is formed, thereby being able to accurately study the composition of the negative electrode active material with good reproducibility regardless of whether there is charge and discharge.

[0157] [Diaphragm]

[0158] The separator separates the positive electrode from the negative electrode, and allows lithium ions to pass through while preventing current short circuit caused by contact between the two electrodes. The separator is formed by a porous film, and the porous film is composed of, for example, a synthetic resin or a ceramic. The separator may also have a laminated structure formed by laminating two or more porous films. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, polyethylene, etc.

[0159] [Electrolyte]

[0160] At least a portion of the active material layer or the separator is impregnated with a liquid electrolyte (electrolyte solution). The electrolyte solution is an electrolyte salt dissolved in a solvent and may contain other materials such as additives.

[0161] The solvent can use a non-aqueous solvent, for example. As the non-aqueous solvent, for example, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane or tetrahydrofuran can be listed. Among them, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. The reason is that better characteristics can be obtained. In addition, at this time, by combining high viscosity solvents such as ethylene carbonate and propylene carbonate with low viscosity solvents such as dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate, more excellent characteristics can be obtained. This is because the dissociation of the electrolyte salt or the ion mobility is improved.

[0162] As the solvent additive, preferably comprises unsaturated carbon bond cyclic carbonate. The reason is that, during charge and discharge, a stable coating is formed on the negative electrode surface, thereby being able to suppress the decomposition reaction of the electrolyte. As the unsaturated carbon bond cyclic carbonate, for example, vinylene carbonate or vinyl ethylene carbonate etc. can be listed.

[0163] Furthermore, as the solvent additive, it is preferable to contain sultone (cyclic sulfonate) because the chemical stability of the battery is improved. Examples of sultone include propane sultone and propene sultone.

[0164] Furthermore, the solvent preferably contains an acid anhydride. This is because the chemical stability of the electrolyte solution is improved. Examples of the acid anhydride include propane disulfonic anhydride.

[0165] The electrolyte salt may include at least one of light metal salts such as lithium salts. Examples of lithium salts include lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4).

[0166] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent because high ion conductivity can be obtained.

[0167] [Method for producing laminated film type secondary battery]

[0168] Initially, the positive electrode is made using the above-mentioned positive electrode material. First, the positive electrode active material is mixed with the positive electrode binder, positive electrode conductive aid, etc. added as needed to form a positive electrode mixture, and then dispersed in an organic solvent to form a positive electrode mixture slurry. Next, the mixture slurry is applied to the positive electrode collector using a coating device such as a die coater with a knife roller or a die head, and then hot air drying is performed to obtain a positive electrode active material layer. Finally, the positive electrode active material layer is compression-molded using a roller press or the like. At this time, heating may also be performed, and compression may be repeated multiple times.

[0169] Next, using the same operation procedure as that for producing the negative electrode 10 for a lithium ion secondary battery, a negative electrode active material layer is formed on the negative electrode collector to produce a negative electrode.

[0170] When making the positive electrode and the negative electrode, each active material layer is formed on both sides of the positive electrode and the negative electrode current collector. At this time, in any electrode, the active material coating lengths on both sides can be different (refer to Figure 1 ).

[0171] Next, prepare the electrolyte. Next, install the positive lead 32 on the positive electrode collector by ultrasonic welding or the like, and install the negative lead 33 on the negative electrode collector. Next, stack or wind the positive electrode and the negative electrode through a separator to make a wound electrode body 31, and adhere a protective tape to its outermost periphery. Next, form the wound body in a flat shape. Next, after sandwiching the wound electrode body between the folded film-like outer packaging members 35, the insulating parts of the outer packaging members are bonded to each other by a thermal welding method, and the wound electrode body is sealed in an open state in only one direction. Next, insert a sealing film between the positive and negative electrode leads and the outer packaging member. Next, a specified amount of the above-prepared electrolyte is added from the open portion for vacuum impregnation. After impregnation, the open portion is bonded by a vacuum thermal welding method. The laminated film type secondary battery 30 can be manufactured in the above manner.

[0172] In the non-aqueous electrolyte secondary battery of the present invention such as the laminated film type secondary battery 30 prepared above, the negative electrode utilization rate during charge and discharge is preferably 93% or more and 99% or less. If the negative electrode utilization rate is set in a range of more than 93%, the initial charging efficiency will not decrease, and the battery capacity can be increased. In addition, if the negative electrode utilization rate is set in a range of less than 99%, Li will not precipitate, and safety can be ensured.

[0173] Example

[0174] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples of the present invention, but the present invention is not limited to these Examples.

[0175] (Example 1-1)

[0176] Through the following steps, Figure 3 A laminated film type secondary battery 30 is shown.

[0177] The positive electrode was first prepared. For the positive electrode active material, the positive electrode mixture was prepared by mixing the following components: 95 parts by mass of lithium nickel cobalt aluminum composite oxide (LiNi 0.7 Co 0.25 Al 0.05 O), 2.5 parts by mass of positive electrode conductive aid (acetylene black) and 2.5 parts by mass of positive electrode binder (polyvinylidene fluoride, PVDF). Then, the positive electrode mixture is dispersed in an organic solvent (N-methyl-2-pyrrolidone, NMP) to make a paste slurry. Then, a coating device with a die head is used to apply the slurry on both sides of the positive electrode collector, and a hot air drying device is used for drying. At this time, the positive electrode collector uses a collector with a thickness of 15μm. Finally, a roller press is used for compression molding.

[0178] Next, make a negative electrode. First, make a silicon-based active material in the following manner. A raw material (vaporized starting material) made by mixing metallic silicon and silicon dioxide is placed in a reactor, and the vaporized material in an atmosphere of a vacuum degree of 10 Pa is deposited on an adsorption plate and then fully cooled, and the deposit is taken out and crushed using a ball mill. Next, lithium is inserted into the silicon compound particles by a redox method to modify the silicon compound. First, the negative electrode active material particles are immersed in a solution (solution A), which is a solution in which lithium sheets and naphthalene as an aromatic compound are dissolved in tetrahydrofuran (hereinafter referred to as THF). The solution A is prepared by dissolving naphthalene in a THF solvent at a concentration of 0.2 mol / L, and then adding 12% by mass of lithium sheets to the mixed solution of THF and naphthalene. In addition, the temperature of the solution when the negative electrode active material particles are immersed is set to 20°C, and the immersion time is set to 20 hours. Then, the negative electrode active material particles are filtered and taken out. Through the above treatment, lithium is inserted into the negative electrode active material particles.

[0179] The obtained silicon compound particles are heat treated at 650° C. or less for 24 hours in an argon atmosphere to stabilize the Li compound.

[0180] The negative electrode active material particles (silicon-based active material particles) were modified in the above manner and then washed with a solvent. Through the above treatment, negative electrode active material particles were prepared.

[0181] The obtained negative electrode active material particles were subjected to XRD measurement. 29 Si-NMR measurement, Raman spectroscopy analysis, particle size distribution measurement.

[0182] The silicon-based active material and the carbon-based active material prepared in the above manner were mixed in a mass ratio of 2:8 to prepare a negative electrode active material. Among them, as the carbon-based active material, a material obtained by mixing natural graphite covered with a pitch layer and artificial graphite in a mass ratio of 5:5 was used. In addition, the median particle size of the carbon-based active material was 20 μm.

[0183] Next, the prepared negative electrode active material, conductive aid 1 (carbon nanotube, CNT), conductive aid 2 (carbon particles with a median particle size of about 50nm), styrene-butadiene rubber (styrene-butadiene copolymer, hereinafter referred to as SBR), carboxymethyl cellulose (hereinafter referred to as CMC) were mixed at a dry mass ratio of 92.5:1:1:2.5:3, and then diluted with pure water to prepare a negative electrode mixture slurry. In addition, the above-mentioned SBR and CMC are negative electrode binders (negative electrode bonding agents).

[0184] In addition, electrolytic copper foil (thickness 15 μm) was used as the negative electrode collector. Finally, the negative electrode mixture slurry was applied to the negative electrode collector and dried in a vacuum atmosphere at 100°C for 1 hour. The deposition amount of the negative electrode active material layer per unit area on one side of the dried negative electrode (also called area density) was 5 mg / cm 2 .

[0185] Next, fluoroethylene carbonate (FEC), ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed as solvents, and electrolyte salt (lithium hexafluorophosphate: LiPF6) was dissolved to prepare an electrolyte solution. At this time, the composition of the solvent was FEC:EC:DEC=1:2:7 in volume ratio, and the content of the electrolyte salt was 1.0 mol / kg relative to the solvent. Furthermore, 1.5% by mass of vinylene carbonate (VC) was added to the obtained electrolyte solution.

[0186] Next, assemble the secondary battery in the following manner. Initially, ultrasonically weld the aluminum lead to one end of the positive electrode collector, and weld the nickel lead to the negative electrode collector. Next, stack the positive electrode, separator, negative electrode, and separator in sequence, and then wind them in the length direction to obtain a wound electrode body. Fix the end of its winding with a PET protective tape. The separator uses a 12μm laminated film, which is formed by sandwiching a film with a porous polyethylene as the main component with a film with a porous polypropylene as the main component. Next, after the electrode body is clamped between the outer packaging members, the outer peripheral portions except one side are heat-fused to each other, and then the electrode body is housed inside. The outer packaging member uses an aluminum laminated film stacked with a nylon film, an aluminum foil, and a polypropylene film. Next, the prepared electrolyte is injected from the opening, impregnated in a vacuum atmosphere, and then heat-fused and sealed.

[0187] The cycle characteristics and initial charge and discharge characteristics of the secondary battery produced in the above manner were evaluated.

[0188] The cycle characteristics are examined in the following manner. First, in order to stabilize the battery, two cycles of charge and discharge are performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle is measured. Next, charge and discharge are performed until the total number of cycles is 299 cycles, and the discharge capacity is measured each time. Finally, the discharge capacity of the 300th cycle obtained by charging and discharging at 0.2C is divided by the discharge capacity of the second cycle, and the capacity retention rate (hereinafter referred to as the retention rate) is calculated. Normally, the cycle, that is, from the 3rd cycle to the 299th cycle, is charged and discharged at 0.7C and discharged at 0.5C.

[0189] When examining the initial charge and discharge characteristics, the initial efficiency (sometimes also called initial efficiency) is calculated. The initial efficiency is calculated by the following formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) × 100. The atmosphere temperature is the same as when examining the cycle characteristics. In addition, the initial efficiency is the efficiency calculated based on the discharge capacity to 1.2V.

[0190] (Examples 1-2, 1-3, Comparative Examples 1-1, 1-2)

[0191] The carbon coating coverage was adjusted by adjusting the temperature and time conditions when washing with the modified solvent as shown in Table 1. A secondary battery was prepared under the same conditions as in Example 1-1 and each evaluation was performed. As shown in the results shown in Table 1, in the case of SiO xIn the silicon compounds shown, the carbon coverage was greater than 0 mass % and less than 1 mass %, and good initial efficiency and capacity retention were obtained. In Comparative Example 1-1 with a carbon coverage of 1.2 mass %, it was found that the initial efficiency and capacity retention decreased due to the side reaction of the carbon coating during charge and discharge. In Comparative Example 1-2 with a carbon coverage of 0 mass %, conductivity could not be obtained, resulting in poor initial efficiency and capacity retention.

[0192] [Table 1]

[0193] SiO x x=1, D50=7.4μm, Ie / Ic=18.4

[0194] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm

[0195] Modification method: Redox method

[0196]

[0197] (Examples 2-1 to 2-4)

[0198] As shown in Table 2, the Ia / Ib intensity ratio of the negative electrode active material particles was adjusted. This adjustment can be adjusted by the heat treatment conditions (temperature, pressure) after lithium insertion. In addition, a secondary battery was made under the same conditions as in Example 1-1, and each evaluation was performed, and the results are shown in Table 2.

[0199] [Table 2]

[0200] SiO x x=1, D50=7.4μm, Ie / Ic=18.4

[0201] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm

[0202] Modification method: Redox method

[0203]

[0204] As shown in Table 2, particularly good initial efficiency and capacity retention rate were obtained in the range of 0≤Ia / Ib≤3.0. Since compounds with OC=O bonds are the main cause of side reactions caused by carbon coating during charging, by not too much compound with OC=O bonds, side reactions can be suppressed, and the initial efficiency and capacity retention rate are improved. On the other hand, in Examples 2-4 where Ia / Ib>3.0, since the number of compounds with OC=O bonds increases, the side reactions caused by carbon coating during charging increase, and the initial efficiency and capacity retention rate both decrease slightly. From the above results, it can be seen that Ia / Ib is preferably in the range of 0≤Ia / Ib≤3.0.

[0205] (Examples 3-1 to 3-7)

[0206] As shown in Table 3, the XRD intensity ratio of Li2SiO3 as a Li compound was adjusted. This adjustment was implemented by adjusting the amount of lithium insertion. In addition, a secondary battery was prepared under the same conditions as in Example 1-1, and each evaluation was performed, and the results are shown in Table 3.

[0207] [Table 3]

[0208] SiO x x=1, D50=7.4μm, Ia / Ib=2.0

[0209] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm

[0210] Modification method: Redox method

[0211]

[0212] As shown in Table 3, by reducing Ie / Ic, the initial efficiency and capacity retention rate are improved. As the amount of Li inserted increases, the XRD intensity ratio of Li2SiO3 becomes smaller, which is due to the further modification of the irreversible components of the silicon compound. On the other hand, although not recorded in the table, when the intensity ratio Ie / Ic is greater than 1, the doped Li is more stabilized, and the generation of gas in the aqueous slurry can be suppressed, so it is preferably set in a manner that the intensity ratio Ie / Ic is greater than 1.

[0213] (Examples 4-1 to 4-6)

[0214] Next, the half-peak width of Li2SiO3 obtained by XRD spectrum was adjusted as shown in Table 4. This adjustment can be adjusted by the Li content. In addition, a secondary battery was made under the same conditions as in Example 1-1, and each evaluation was performed, and the results are shown in Table 4.

[0215] [Table 4]

[0216] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0217] Si crystallite size = 1.8nm

[0218] Modification method: Redox method

[0219]

[0220] If the half-peak width exceeds 3.0°, the Li content increases and the half-peak width of Li2SiO3 becomes wider. At this time, the slurry generates gas significantly, resulting in a decrease in battery characteristics. The half-peak width of Li2SiO3 is preferably greater than 0.5° and less than 3.0°.

[0221] (Examples 5-1 to 5-5)

[0222] Next, the crystallite size of the Si (220) plane was adjusted as shown in Table 5. This adjustment can be adjusted by the heat load of the silicon oxide. In addition, a secondary battery was produced under the same conditions as in Example 1-1, and various evaluations were performed. The results are shown in Table 5.

[0223] [Table 5]

[0224] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0225] Li2SiO3 half peak width = 1.3°

[0226] Modification method: Redox method

[0227]

[0228] As shown in Table 5, when the crystallite size is within the range of 5 nm or less, the capacity retention rate shows good results.

[0229] (Examples 6-1 to 6-5)

[0230] Next, If / Ii and Ih / Ii were adjusted as shown in Table 6. This adjustment can be adjusted by the heat treatment conditions of the Li-containing silicon oxide. In addition, a secondary battery was prepared under the same conditions as in Example 1-1, and various evaluations were performed. The results are shown in Table 6.

[0231] [Table 6]

[0232] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0233] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm

[0234] Modification method: Redox method

[0235]

[0236] As shown in Table 6, If / Ii was 0.23 or less and Ih / Ii was 1.1, and the doped Li was sufficiently stabilized, so the binding property with the binder was slightly weakened, and thus the battery characteristics were good as a result.

[0237] (Examples 7-1 to 7-8)

[0238] Next, as shown in Table 7, the intensity ratio Id / Ig of the D band and the G band obtained by Raman spectroscopy analysis, and the intensity ratio ISi / Ig of the Si peak intensity and the G band were adjusted. This adjustment can be adjusted by the conditions (heating conditions, temperature, pressure, gas flow rate) during thermal CVD. In addition, a secondary battery was made under the same conditions as in Example 1-1, and each evaluation was performed, and the results are shown in Table 7.

[0239] [Table 7]

[0240] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0241] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm, If / Ii = 0.05, Ih / Ii = 0.07

[0242] Modification method: Redox method

[0243]

[0244] As shown in Table 7, when Id / Ig is 0 or more and 2.0 or less, the carbon in the diamond structure without conductivity decreases, so the initial efficiency and capacity retention rate are good. In addition, in the range of ISi / Ig being 0 or more and 5 or less, the silicon compound can be fully covered, so the conductivity can be fully ensured, and the initial efficiency and capacity retention rate show good results.

[0245] (Examples 8-1 to 8-7)

[0246] Next, D10 and D50 (median particle size) of the silicon compound particles were changed as shown in Table 8. This adjustment can be adjusted by the degree of pulverization or classification. In addition, a secondary battery was prepared under the same conditions as in Example 1-1, and each evaluation was performed. The results are shown in Table 8.

[0247] [Table 8]

[0248] SiO x x=1, Ia / Ib=2.0, Ie / Ic=18.4

[0249] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm, If / Ii = 0.05, Ih / Ii = 0.07

[0250] Modification method: Redox method

[0251]

[0252] As shown in Table 8, if the median particle size of the silicon compound is greater than 0.5 μm and D10 is greater than 2 μm, the initial efficiency and retention rate are further improved. This is because the surface area per mass of the silicon compound particles is not too large, so side reactions can be suppressed. On the other hand, if the median particle size of the silicon compound is less than 20 μm and D10 is less than 16 μm, the particles are not easy to break during charging, and it is not easy to generate SEI (solid electrolyte interface) caused by the new surface during charging and discharging, so the loss of reversible Li can be suppressed. In addition, when the median particle size of the silicon compound is less than 20 μm, the expansion of the silicon compound particles during charging will not become too large, so the physical and electrical damage to the negative electrode active material layer caused by expansion can be prevented.

[0253] (Examples 9-1 to 9-5)

[0254] Next, Li2CO3 as a Li compound was adjusted as shown in Table 9. Li2CO3 can be adjusted by adjusting the atmospheric exposure time. In addition, a secondary battery was prepared under the same conditions as in Example 1-1, and various evaluations were performed. The results are shown in Table 2.

[0255] [Table 9]

[0256] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0257] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm, If / Ii = 0.05, Ih / Ii = 0.07

[0258] Modification method: Redox method

[0259]

[0260] As shown in Table 9, when the Ij / Ic intensity is 10 or less, the initial efficiency is good and, as a result, the battery characteristics are also good.

[0261] (Examples 10-1 to 10-8)

[0262] Next, as shown in Table 10, hydrocarbon gas was introduced during the heat treatment after the lithium was inserted to form a carbon coating on the surface, and a carbon coating with a different peak position of the G band peak based on Raman spectroscopy analysis was formed on the outermost surface of the silicon compound. The adjustment of the G band peak can be adjusted by the treatment temperature. In addition, a secondary battery was made under the same conditions as in Example 1-1, and each evaluation was performed, and the results are shown in Table 10.

[0263] [Table 10]

[0264] SiO x x=1, D50=7.4μm, Ia / Ib=2.0, Ie / Ic=18.4

[0265] Li2SiO3 half peak width = 1.3°, Si crystallite size = 1.8nm,

[0266] If / Ii=0.05,Ih / Ii=0.07,Ij / Ie=0

[0267] Modification method: Redox method

[0268]

[0269] As shown in Table 10, when the surface of the silicon compound has a G band peak at 1588 cm -1 ~1598cm -1 When the carbon coating is within the range of 1500 to 1500 cm / s, the conductivity is improved, and the dissolution of Li from the Li compound can be further suppressed, so that the pH value in the aqueous slurry can be suppressed, thereby improving the stability of the aqueous slurry. By using this slurry, a better electrode can be obtained, and as a result, good battery characteristics can be obtained. When the G band peak is greater than 1598 cm / s -1 1600cm -1 When the Li compound is not sufficiently stabilized, the conductivity of the formed carbon film is also insufficient, resulting in a slight deterioration in battery characteristics.

[0270] This manual contains the following protocols.

[0271] [1] A negative electrode active material for a non-aqueous electrolyte secondary battery, characterized in that:

[0272] It has negative electrode active material particles,

[0273] The negative electrode active material particles contain silicon compound particles, and the silicon compound particles contain silicon compound (SiO x , 0.5≤x≤1.6),

[0274] The silicon compound particles contain a Li compound,

[0275] At least a portion of the negative electrode active material particles is covered with a carbon coating.

[0276] The coverage amount of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating,

[0277] The carbon coating includes a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond,

[0278] The silicon compound particles include crystalline Li 2 SiO 3 as the Li compound.

[0279] [2] A negative electrode active material for a non-aqueous electrolyte secondary battery as described in [1] above, wherein the intensity ratio of the intensity Ia at around 290 eV derived from the OC=O bond and the intensity Ib at around 285 eV derived from the CC bond obtained by X-ray photoelectron spectroscopy of the negative electrode active material is 0≤Ia / Ib≤3.0.

[0280] [3] A negative electrode active material for a non-aqueous electrolyte secondary battery as described in [1] or [2] above, wherein the intensity Ie of the negative electrode active material derived from Li2SiO3 near 2θ=18.7° obtained by X-ray diffraction satisfies 1≤Ie / Ic≤18.5 relative to the intensity Ic derived from Si near 2θ=47.5°.

[0281] [4] A negative electrode active material for a non-aqueous secondary battery as described in any one of [1] to [3] above, wherein the half-width of the peak derived from Li2SiO3 near 2θ=18.7° obtained by X-ray diffraction of the negative electrode active material is greater than or equal to 0.5° and less than or equal to 3.0°.

[0282] [5] The negative electrode active material for a non-aqueous secondary battery as described in any one of [1] to [4] above, wherein the crystallite size derived from the Si (220) crystal plane obtained by X-ray diffraction of the negative electrode active material is 5 nm or less.

[0283] [6] The negative electrode active material for a non-aqueous secondary battery as described in any one of [1] to [5] above, wherein

[0284] In the negative electrode active material 29 At least one of the chemical shift values ​​obtained by the Si-MAS-NMR spectrum in the region of -80 ppm to less than -70 ppm, -70 ppm to less than -60 ppm, and -60 ppm to less than -30 ppm has at least one peak.

[0285] [7] The negative electrode active material for a non-aqueous secondary battery according to [6] above, wherein

[0286] In the negative electrode active material 29 When the peak intensity of the peak obtained in the region where the chemical shift value obtained by Si-MAS-NMR spectrum is greater than -60 ppm and less than -30 ppm is defined as If, the peak intensity of the peak obtained in the region where the chemical shift value is greater than -70 ppm and less than -60 ppm is defined as Ih, and the peak intensity of the peak obtained in the region where the chemical shift value is greater than -80 ppm and less than -70 ppm is defined as Ii,

[0287] Satisfies: 0≤If / Ii≤0.23 and 0≤Ih / Ii≤1.1.

[0288] [8] The negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of [1] to [7] above, wherein the intensity ratio Id / Ig of the D band to the G band obtained by Raman spectroscopy of the negative electrode active material is 0≤Id / Ig≤2.0.

[0289] [9] The negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of [1] to [8] above, wherein the intensity ratio ISi / Ig of the Si peak intensity to the G band obtained by Raman spectroscopy of the negative electrode active material is 0≤ISi / Ig≤5.0.

[0290]

[10] The negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of [1] to [9] above, wherein the median particle size of the silicon compound particles is 0.5 μm or more and 20 μm or less.

[0291]

[11] The negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of [1] to

[10] above, wherein the negative electrode active material particles do not contain Li2CO3, or

[0292] A portion of its outermost layer is covered with crystalline Li2CO3, and the peak intensity Ij of the negative electrode active material particles obtained by X-ray diffraction originating from Li2CO3 near 2θ=21° satisfies 0≤Ij / Ic≤10 relative to the intensity Ic originating from Si near 2θ=47.5°.

[0293]

[12] The negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of [1] to

[11] above, wherein the negative electrode active material is covered with a carbon layer different from the carbon coating.

[0294]

[13] A negative electrode active material for a non-aqueous electrolyte secondary battery as described in any one of [1] to

[12] above, wherein the peak derived from the G band obtained by Raman spectroscopy of the negative electrode active material is 1588 cm -1 ~1598cm -1 of carbon film covering.

[0295]

[14] A non-aqueous electrolyte secondary battery, characterized in that it contains the negative electrode active material for a non-aqueous electrolyte secondary battery according to any one of [1] to

[13] above.

[0296]

[15] A mobile terminal comprising the non-aqueous electrolyte secondary battery described in

[14] above.

[0297]

[16] An electric vehicle comprising the non-aqueous electrolyte secondary battery described in

[14] above.

[0298]

[17] A power storage system comprising the non-aqueous electrolyte secondary battery described in

[14] above.

[0299]

[18] A method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, which is a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery containing negative electrode active material particles, characterized in that the production method comprises:

[0300] Preparation of silicon compounds (SiO x : 0.5≤x≤1.6) and

[0301] a step of inserting Li into the silicon compound particles to generate Li2SiO3 as a Li compound,

[0302] The method further comprises the step of covering at least a portion of the silicon compound particles with a carbon coating, simultaneously with or after the step of inserting Li into the silicon compound particles.

[0303] The carbon coating is used for covering in the following manner: the coverage of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, and the carbon coating is a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond.

[0304]

[19] The method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery according to

[18] above, wherein the step of inserting Li into the silicon compound particles is performed by an electrochemical method or a method based on a redox reaction.

[0305] The present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same configuration and exhibiting the same functions and effects as the technical concept described in the claims of the present invention are all within the technical scope of the present invention.

Claims

1. A negative electrode active material for a non-aqueous electrolyte secondary battery, characterized in that It has negative electrode active material particles, The negative electrode active material particles contain silicon compound particles, and the silicon compound particles contain SiO x , where 0.5≤x≤1.6, The silicon compound particles contain a Li compound, At least a portion of the negative electrode active material particles is covered with a carbon coating. The coverage amount of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, The carbon coating includes a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond, The silicon compound particles include crystalline Li 2 SiO 3 as the Li compound.

2. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, characterized in that The intensity ratio of intensity Ia at around 290 eV derived from OC═O bond and intensity Ib at around 285 eV derived from CC bond of the negative electrode active material obtained by X-ray photoelectron spectroscopy is 0≤Ia / Ib≤3.

0.

3. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The intensity Ie of the negative electrode active material at around 2θ=18.7° derived from Li2SiO3 obtained by X-ray diffraction satisfies 1≤Ie / Ic≤18.5 relative to the intensity Ic at around 2θ=47.5° derived from Si.

4. The negative electrode active material for a non-aqueous secondary battery according to claim 3, characterized in that: The half-value width of the peak derived from Li 2 SiO 3 at 2θ=18.7° obtained by X-ray diffraction of the negative electrode active material is greater than or equal to 0.5° and less than or equal to 3.0°.

5. The negative electrode active material for a non-aqueous secondary battery according to claim 1 or 2, characterized in that: The crystallite size of the negative electrode active material derived from the Si (220) crystal plane obtained by X-ray diffraction is 5 nm or less.

6. The negative electrode active material for a non-aqueous secondary battery according to claim 1 or 2, characterized in that: In the negative electrode active material 29 The chemical shift values ​​obtained by the Si-MAS-NMR spectrum have at least one peak in at least one region among the region of -80 ppm to less than -70 ppm, the region of -70 ppm to less than -60 ppm, and the region of -60 ppm to less than -30 ppm.

7. The negative electrode active material for a non-aqueous secondary battery according to claim 6, characterized in that: In the negative electrode active material 29 When the peak intensity of the peak obtained in the region of the chemical shift value obtained in the Si-MAS-NMR spectrum of not less than -60 ppm and less than -30 ppm is defined as If, the peak intensity of the peak obtained in the region of the chemical shift value not less than -70 ppm and less than -60 ppm is defined as Ih, and the peak intensity of the peak obtained in the region of the chemical shift value not less than -80 ppm and less than -70 ppm is defined as Ii, Satisfies: 0≤If / Ii≤0.23 and 0≤Ih / Ii≤1.

1.

8. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The intensity ratio Id / Ig of the D band and the G band of the negative electrode active material obtained by Raman spectroscopy analysis is 0≤Id / Ig≤2.

0.

9. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The negative electrode active material has an intensity ratio ISi / Ig of Si peak intensity to G band obtained by Raman spectroscopy analysis, which is 0≤ISi / Ig≤5.

0.

10. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The silicon compound particles have a median particle size of 0.5 μm or more and 20 μm or less.

11. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The negative electrode active material particles do not contain Li2CO3, or A portion of its outermost layer is covered with crystalline Li2CO3, and the peak intensity Ij of the negative electrode active material particles obtained by X-ray diffraction originating from Li2CO3 near 2θ=21° satisfies 0≤Ij / Ic≤10 relative to the intensity Ic originating from Si near 2θ=47.5°.

12. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: It is covered with a carbon layer different from the carbon coating.

13. The negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, characterized in that: The peak from the G band obtained by Raman spectroscopy of the negative electrode active material is 1588 cm -1 ~1598cm -1 of carbon film covering.

14. A non-aqueous electrolyte secondary battery, characterized in that: The negative electrode active material comprises the negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2.

15. A mobile terminal, characterized in that: The battery comprises the nonaqueous electrolyte secondary battery according to claim 14.

16. An electric vehicle, characterized in that: The battery comprises the nonaqueous electrolyte secondary battery according to claim 14.

17. An electric power storage system, characterized in that: The battery comprises the nonaqueous electrolyte secondary battery according to claim 14.

18. A method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery, which is a method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery containing negative electrode active material particles, characterized in that: The manufacturing method comprises: Preparation of SiO containing silicon compounds x The process of producing silicon compound particles, wherein 0.5≤x≤1.6; and a step of inserting Li into the silicon compound particles to generate Li2SiO3 as a Li compound, The method further comprises the step of covering at least a portion of the silicon compound particles with a carbon coating, simultaneously with or after the step of inserting Li into the silicon compound particles. The carbon coating is used for covering in the following manner: the coverage of the carbon coating on the negative electrode active material particles is greater than 0 mass % and less than 1 mass % relative to the total of the silicon compound particles and the carbon coating, and the carbon coating is a coating composed of at least one of a compound having an OC=O bond and a compound having a CC bond.

19. The method for producing a negative electrode active material for a non-aqueous electrolyte secondary battery according to claim 18, characterized in that: The process of inserting Li into the silicon compound particles is performed by an electrochemical method or a method based on a redox reaction.

Citation Information

Patent Citations

  • Negative electrode material for nonaqueous secondary battery and its manufacturing method, and lithium ion secondary battery

    JP2011222153A

  • Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method of negative electrode material for nonaqueous electrolyte secondary battery

    JP2020113495A